Malignancy Rates by Bethesda Subcategory in the Pediatric Population. (November 2022) - Park, Soyun; Osterbauer, Beth; Sahyouni, Grace; Paik, Connie; Austin, Juliana; Gomez, Gabriel; Shillingford, Nick; Kwon, Daniel
Introduction: While the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) is the most widely used method for categorizing thyroid nodules, its applicability to children is often debated. We describe our institution's experience utilizing the TBSRTC and examine the rates of malignancy in our population. Methods: We conducted a retrospective chart review of eligible patients undergoing primary thyroidectomy at a high-volume tertiary care pediatric hospital. All patients had pre-operative fine needle aspiration Results: Of the 112 patients in our cohort, 85 (76%) were female. The median age was 15.1 years. The patients were divided into groups based on the Bethesda categorization of the fine needle aspirations of their nodules. The percentages of patients whose resection specimens showed evidence of malignancy on the surgical pathology reports were recorded as follows: category I (n = 5): 20%, category II (n = 11): 0%, category III (n = 30): 17%, category IV (n = 13): 31%, category V (n = 17): 94% and category VI (n = 36): 100%. Conclusion: Our findings indicate that the malignancy rates at our institution are comparable to those reported by other high-volume studies. When compared with the 2017 TBSRTC data, we found that our results were similar in many categories, with the exception of categories I and V.